Study of prevalence and factors affecting prevalence of attention deficit hyperactivity disorder in primary school children - Singanamala, Harish; P., Naveen Kumar; P. V., Sridhar; P. S., Thammanna (International Journal of Contemporary Pediatrics, 2021)
Background: Attention deficit hyperactivity disorder is a commonly diagnosed neurobehavioral disorder in school age children. ADHD can even persist to adulthood and if left untreated can lead to negative impact not only on health but also on socioeconomic life of patients. Over the past 2 decades there have been 19 community-based studies offering estimates of prevalence ranging from 2% to 17%. Current study was aimed to estimate the prevalence and factors affecting ADHD along with the applicability of a DSM-4 based questionnaire for detecting ADHD. Methods: Current investigation is a crossectional retrospective study conducted on 1150 children’s at two primary schools in the district of Gulbarga. School children between the age range of 7 to 12 years were screened over duration of one year and six months using Conner’s parent and teacher rating scale. Students above 65 score as per the scale were considered positive and were interviewed using DSM-4 criteria. Results: Fifty-eight (5.04%) children satisfied the criteria to be diagnosed as ADHD when interviewed with DSM-4 criteria. Males were observed to be more prone to have ADHD than females. The mean age of ADHD children was between 9 to 10 years. Major effective factors for ADHD were found to be maternal stress during pregnancy, pampering the child and addiction of playing videos games. Conclusions: Prevalence studies can aid in formulating recommendations for future clinical practice and also assist in clarifying whether the patterns of ADHD diagnosis and treatment in community settings are appropriate.